Strategies and issues in sustainable business management - I., Sundar, Dr.; Ajith Kumar, D. J. (Universiti Malaysia Perlis (UniMAP), 2011)
The Second International Conference on the Roles of Humanities and Social Science in Engineering (ICoHSE 2010) organized by Universiti Malaysia Perlis (UniMAP), 12th - 14th November 2010 at Bayview Beach Resort, Penang, Malaysia.